Method for preparing bismuth ferrite-based thin film with high self-polarization piezoelectric property through multi-element equal-ratio solid solution
Bismuth ferrite-based films with multi-element solid solutions address the limitations of existing piezoelectric films by achieving high self-polarization and piezoelectric coefficients, suitable for MEMS devices.
Patent Information
- Application Number
- CN202411278961.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-12
AI Technical Summary
Existing piezoelectric films, such as ScAlN and PZT, have limitations in piezoelectric coefficients and stability under high-temperature semiconductor processing, and PZT's lead content poses environmental and health risks, necessitating the development of lead-free materials with superior piezoelectric properties and spontaneous polarization.
A method for preparing bismuth ferrite-based films through a sol-gel process with multi-element isotropic solid solutions, replacing B-site elements with multiple cations in equal proportions to induce dislocation defects, pinning electric dipoles and achieving high self-polarization and piezoelectric coefficients.
The method produces ferroelectric films with excellent self-polarization and piezoelectric performance, overcoming depolarization issues in high-temperature processes and offering broad application prospects in electronic materials, particularly in MEMS devices.
Smart Images

Figure CN119156111A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of piezoelectric thin film materials, and relates to a method for preparing a bismuth ferrite-based thin film with high self-polarization piezoelectric performance by multi-element isotropic solid solution. Background Art
[0002] Ferroelectric materials are the key medium for the mutual conversion of electrical energy and mechanical energy, and play a vital role in the realization of mechatronics and intelligent structural components. With the development of nanotechnology, materials are developing in the direction of low dimension, small size and multi-function. Micro-electromechanical systems (MEMS) based on ferroelectric films are widely used in radar, transducer, sonar, speakers and other fields.
[0003] As the core functional unit of MEMS, the development of piezoelectric films is crucial. The wurtzite-structured ScAlN piezoelectric film occupies a significant market share due to its stability and compatibility with semiconductor Si processes. However, its piezoelectric coefficient is usually less than 30pC / N, which greatly limits the further improvement of the signal sensitivity of related devices. Therefore, it is urgent to explore more alternative piezoelectric films with different structures and excellent piezoelectric properties.
[0004] Perovskite ferroelectric materials are being widely studied due to their simple structural characteristics and excellent piezoelectric properties. 3 (PZT) is the most commonly used perovskite ferroelectric material in the commercial industry. PZT ferroelectric film has excellent piezoelectric properties, and its piezoelectric coefficient is as high as 200pC / N. However, compared with ScAlN film, the acquisition of the piezoelectric system coefficient in PZT film usually requires the application of a sufficient DC electric field for polarization for about 30 minutes. However, the semiconductor industry based on Si substrates usually requires processes such as welding and packaging at temperatures exceeding 260°C before obtaining the final device. Under this high-temperature operation, ferroelectric films such as PZT are very easy to depolarize and fail. Therefore, compared with piezoelectric materials such as ScAlN that do not require polarization, despite its better piezoelectric properties, its application has never made a significant breakthrough. In addition, since PZT itself contains lead, it is harmful to the human body and the environment, and it is also extremely important to seek alternative lead-free materials.
[0005] In summary, breaking through the polarization process limitations of ferroelectric films such as PZT, obtaining environmentally friendly perovskite ferroelectric films that can be spontaneously polarized, and obtaining piezoelectric coefficients that are superior to those of ScAlN films is one of the bottlenecks in the development of the MEMS field today. Summary of the invention
[0006] The present invention provides a method for preparing bismuth ferrite (BiFeO) with high self-polarization piezoelectric performance by multi-element isotropic solid solution. 3The method adopts a sol-gel method to prepare a bismuth ferrite-based ferroelectric film in which multiple elements are solid-dissolved in equal proportions, and induces B-site related dislocation defects by replacing the B-site (Fe) element with more than three elements in equal proportions, thereby unidirectionally pinning the electric dipole in the three-dimensional structure of the film, thereby obtaining a ferroelectric film with self-polarization performance, high piezoelectric coefficient and good repeatability.
[0007] The technical solution of the present invention is as follows:
[0008] The method for preparing a bismuth ferrite-based film with high self-polarization piezoelectric performance by multi-element isotropic solid solution comprises the following steps:
[0009] (1) Preparation of sol: Solid solution of BiFeO in equal proportions of multiple elements 3 The raw materials are dissolved in an organic solvent in a stoichiometric ratio, and then a chemical chelating stabilizer is added, stirred until the mixture is uniform, filtered, sealed, and allowed to stand at room temperature for aging to obtain a clear, transparent, uniform and stable multi-element equipotent solid solution BiFeO 3 Precursor sol, the multi-element equiproportional solid solution BiFeO 3 To replace the B site (i.e., Fe site) with three or more cations in BiFeO 3 The replacement method is to replace all the replacement cations in equal proportion or according to the weighted stoichiometric ratio, and the replacement cation is selected from Fe 3+ Sc 3+ , Ga 3+ 、Al 3+ , Mn 3+ 、Ni 2+ and Ti 4+ Three or more of the following;
[0010] (2) Spinning film: Multi-element solid solution BiFeO 3 The precursor sol is spin-coated on the substrate to form a film, and then a multi-element equiproportional solid solution BiFeO is coated. 3 The substrate of the precursor sol was initially solidified at 150±5℃ to obtain a multi-element isotropic solid solution of BiFeO 3 Precursor sol film;
[0011] (3) Heat treatment: Apply the multi-element equal-ratio solid solution BiFeO in step (3) 3 The substrate of the precursor sol film is heat treated, first drying at 120℃~300℃ for 30s~2min, then pyrolyzing at 200℃~500℃ for 1~5min, and finally annealing at 500℃~900℃ for 1~15min, and after cooling, a multi-element isotropic solid solution BiFeO is obtained. 3 Piezoelectric film.
[0012] Preferably, in step (1), the organic solvent is selected from one or a combination of ethylene glycol methyl ether, acetic acid and ethylene glycol. In a specific embodiment of the present invention, ethylene glycol methyl ether is taken as an example.
[0013] Preferably, in step (1), the chemical chelating stabilizer is one or a combination of acetylacetone and citric acid, and the chemical chelating stabilizer and the multi-element solid solution BiFeO 3 The molar ratio of the cations in the reaction mixture is 1: 1. In a specific embodiment of the present invention, acetylacetone is taken as an example.
[0014] Preferably, in step (1), the stirring temperature is 25 to 80° C. and the stirring time is 0.5 to 1 h.
[0015] Preferably, in step (1), multiple elements are solid-dissolved in equal proportions in BiFeO 3 The concentration of the precursor sol is 0.01-0.5 mol / L.
[0016] Preferably, in step (1), multiple elements are solid-dissolved in equal proportions in BiFeO 3 BiFe 1 / 3 Sc 1 / 3 Ga 1 / 3 O 3 、Bi(Fe 1 / 3 Sc 1 / 3 Ga 1 / 3 ) 0.99 Al 0.01 O 3 、Bi(Fe 1 / 3 Sc 1 / 3 Ga 1 / 3 ) 0.99 Mn 0.01 O 3 、BiFe 1 / 3 Sc 1 / 3 (Ni 0.5 Ti 0.5 ) 1 / 3 O 3 、BiFe 1 / 4 Sc 1 / 4 Ga 1 / 4 Al 1 / 4 O 3 or BiFe 1 / 3 Ga 1 / 3 (Ni 0.5 Ti 0.5 ) 1 / 3 O 3 .
[0017] Preferably, in step (1), the raw materials are bismuth nitrate and a combination of three or more of ferric nitrate, scandium nitrate, gallium acetylacetonate, aluminum nitrate, manganese acetate, nickel nitrate and titanium isopropoxide.
[0018] Preferably, in step (2), the spin coating method is firstly to spin coat at a low speed of 200 to 800 r / min for 5 to 20 s, and then to spin coat at a high speed of 2000 to 8000 r / min for 20 to 40 s.
[0019] Preferably, in step (2), the initial curing time is 10 s to 2 min.
[0020] Preferably, in step (3), the heating rate is 10 to 150°C / s, the cooling rate is 0.5 to 3°C / s, and the heat treatment atmosphere is air, oxygen or nitrogen.
[0021] Preferably, the multi-element isotropic solid solution of BiFeO is regulated by controlling the number of repetitions of step (2) and step (3). 3 The thickness of the base piezoelectric film is preferably 2 to 50 times.
[0022] Compared with the prior art, the present invention has the following advantages:
[0023] (1) The present invention prepares multi-element isotropic solid solution BiFeO by sol-gel method 3 The ferroelectric film has excellent self-polarized piezoelectric performance. The preparation method is simple. The oxide can be synthesized by precisely controlling the stoichiometric ratio at room temperature, and the film can be finely modified by multi-element isotropic solid solution. (2) The multi-element isotropic solid solution BiFeO 3 The piezoelectric film has an excellent self-polarization piezoelectric coefficient (d 33 ), avoiding depolarization in the MEMS high-temperature packaging process, and can be used to make piezoelectric microsensors, actuators, transducers, etc., and has very broad application prospects in the field of electronic material technology; (3) The equipment required for the method of the present invention is simple, easy to use, high in production efficiency, and easy to realize industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 BiFeO is a multi-element equipotent solid solution 3 Schematic diagram of the process for preparing the base sol.
[0025] Figure 2 BiFeO is a multi-element equipotent solid solution 3 Schematic diagram of the process for preparing the base film.
[0026] Figure 3 The multi-element isotropic solid solution BiFeO obtained in Examples 1 to 6 3X-ray diffraction pattern of the base film (a) and the Bi(Fe 1 / 3 Sc 1 / 3 Ga 1 / 3 ) 0.99 Mn 0.01 O 3 Transmission electron microscopy morphology and stress analysis of the film (b).
[0027] Figure 4 The Bi(Fe 1 / 3 Sc 1 / 3 Ga 1 / 3 ) 0.99 Mn 0.01 O 3 Scanning image of the cross-sectional morphology of the film.
[0028] Figure 5 The multi-element isotropic solid solution BiFeO obtained in Examples 1 to 6 3 The self-polarization piezoelectric coefficient (d 33 ) curves, (a)-(f) correspond to Examples 1-6, respectively.
[0029] Figure 6 Pure BiFeO obtained in Comparative Example 1 3 XRD and self-polarization piezoelectric coefficient (d 33 ).
[0030] Figure 7 The ordinary Sc-doped (non-multi-element isotropic solid solution) BiFeO obtained in Comparative Example 2 3 XRD and self-polarization piezoelectric coefficient (d 33 ). DETAILED DESCRIPTION
[0031] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0032] The present invention adopts the method of 3 BiFeO is prepared by adding three or more elements of Sc, Ga, Al, Mn, Ni and Ti to the Fe position for solid solution. 3 The precursor sol is then spin-coated and initially solidified, and finally a BFO-based film is formed through a heat treatment process. As the number of solid solution elements increases in equal proportion, the BiFeO prepared by the preparation method of the present invention increases. 3 The Arrhenius phase appears in the base film. This phase exists in the form of dislocations and can pin the electric dipoles in the film unidirectionally through dislocation stress, thereby causing excellent self-polarization characteristics in the obtained film. In addition, the solid solution of multiple elements increases the structural heterogeneity and makes the phase coexistence complicated, which can accurately control the higher piezoelectric coefficient d 33, which can provide MEMS devices with ferroelectric films with self-polarization characteristics, high piezoelectric coefficients and good reliability.
[0033] Example 1
[0034] BiFe2O3 was prepared by solid solution of Fe, Sc and Ga in equal proportions at the B site. 1 / 3 Sc 1 / 3 Ga 1 / 3 O 3 A method for producing a ferroelectric thin film, comprising the steps of:
[0035] (1)BiFe 1 / 3 Sc 1 / 3 Ga 1 / 3 O 3 Preparation of precursor sol: 1.0673 g bismuth nitrate (Bi(NO 3 ) 3 ·5H 2 O) was added to 6 ml of ethylene glycol methyl ether (C 3 H 8 O 2 , 2moe) in beaker A, and start stirring at 500r / min at room temperature (25°C); after it is completely dissolved, add 0.2694g of ferric nitrate (Fe(NO 3 ) 3 9H 2 O) and 0.1660 g of scandium nitrate (Sc(NO 3 ) 3 ·xH 2 O), and continue stirring until completely dissolved. In addition, 0.2447 g of gallium acetylacetonate (C 15 H 21 O 6 Ga) was added to beaker B containing 4 ml of ethylene glycol methyl ether, and the heating temperature was set at 45-70 ° C and stirred for 10 min until it was completely dissolved. After the beakers A and B were completely dissolved and stirred for 30 min each, the two were mixed and 0.4025 ml of acetylacetone was added. After stirring for 4 h at room temperature, the solution was filtered and sealed in a reagent bottle and aged at room temperature for 48 hours to obtain a uniform and stable BiFe 1 / 3 Sc 1 / 3 Ga 1 / 3 O 3 The precursor sol has a sol concentration of 0.2M and an excess of 10% of Bi.
[0036] (2) Substrate thermal activation treatment: First, Pt / Ti / SiO 2After the Si substrate is cleaned and dried, it is placed in a rapid annealing furnace for annealing: the heating rate is 37.5°C / s, annealing at 400°C for 1 minute, and then cooled to room temperature in the furnace.
[0037] (3) Using a sizing machine, the BiFe 1 / 3 Sc 1 / 3 Ga 1 / 3 O 3 Precursor sol spin coating in step (2) Pt / Ti / SiO 2 / Si substrate, the coating procedure was set to low speed 600r / min, time 10s, high speed 4000r / min, spin coating time 30s, and BiFe 1 / 3 Sc 1 / 3 Ga 1 / 3 O 3 Precursor sol-gel film.
[0038] (4) BiFe 1 / 3 Sc 1 / 3 Ga 1 / 3 O 3 The precursor sol film was placed in a rapid annealing furnace for heat treatment: heating rate 17.5°C / s, drying at 200°C for 2 minutes, pyrolysis at 400°C for 5 minutes, and annealing at 550°C for 5 minutes.
[0039] (5) Repeat steps (3) and (4) 15 times to obtain a BiFe 1 / 3 Sc 1 / 3 Ga 1 / 3 O 3 film.
[0040] Example 2
[0041] Bismuth ferrite-based Bi(Fe) was prepared by using Fe, Sc, Ga and Al in equal proportions in solid solution at the B site. 1 / 3 Sc 1 / 3 Ga 1 / 3 ) 0.99 Al 0.01 O 3 The preparation method of the ferroelectric thin film is substantially the same as that of Example 1, except that in step (1), 1% aluminum nitrate (Al(NO 3 ) 3 9H 2 O), producing Bi(Fe 1 / 3 Sc 1 / 3 Ga 1 / 3 ) 0.99 Al 0.01 O 3 film.
[0042] Example 3
[0043] Bismuth ferrite-based Bi(Fe) was prepared by using four elements, Fe, Sc, Ga and Mn, in equal proportions in solid solution at the B site. 1 / 3 Sc 1 / 3 Ga 1 / 3 ) 0.99 Mn 0.01 O 3 The preparation method of the ferroelectric thin film is substantially the same as that of Example 1, except that in step (1), 1% more manganese acetate (MnC 4 H 6 O 4 ·4H 2 O), producing Bi(Fe 1 / 3 Sc 1 / 3 Ga 1 / 3 ) 0.99 Mn 0.01 O 3 film.
[0044] Example 4
[0045] BiFe2O3 was prepared by solid solution of Fe, Sc, Ni and Ti in the B site. 1 / 3 Sc 1 / 3 Ni 1 / 6 Ti 1 / 6 O 3 A method for producing a ferroelectric thin film, comprising the steps of:
[0046] (1)BiFe 1 / 3 Sc 1 / 3 (Ni 0.5 Ti 0.5 ) 1 / 3 O 3 Preparation of precursor sol: 1.0673 g bismuth nitrate (Bi(NO 3 ) 3 ·5H 2 O) was added to 6 ml of ethylene glycol methyl ether (C 3 H 8 O 2 , 2moe) in beaker A, stir at 500r / min at room temperature (25°C), and after it is completely dissolved, add 0.2694g of ferric nitrate (Fe(NO 3 ) 3 9H 2 O) and 0.1660 g of scandium nitrate (Sc(NO 3 ) 3 ·xH 2O), and continue stirring until completely dissolved. In addition, 0.0989 g of nickel nitrate (Ni(NO 3 ) 2 6H 2 O) was added to beaker B containing 4 ml of ethylene glycol methyl ether, and then the temperature was maintained at 25°C and stirred for 2 min until it was completely dissolved, and then 0.1 ml of titanium isopropoxide (Ti[OCH(CH 3 ) 2 ] 4 After the contents in beakers A and B are completely dissolved and stirred for 30 min each, the two are mixed and 0.4025 ml of acetylacetone is added. After stirring for 4 h at room temperature, the solution is filtered and sealed in a reagent bottle. After aging at room temperature for 48 h, a uniform and stable BiFe 1 / 3 Sc 1 / 3 (Ni 0.5 Ti 0.5 ) 1 / 3 O 3 Precursor sol.
[0047] (2) Substrate thermal activation treatment: First, Pt / Ti / SiO 2 After the Si substrate is cleaned and dried, it is placed in a rapid annealing furnace for annealing: the heating rate is 37.5°C / s, annealing at 400°C for 1 minute, and then cooled to room temperature in the furnace.
[0048] (3) Using a sizing machine, the BiFe 1 / 3 Sc 1 / 3 (Ni 0.5 Ti 0.5 ) 1 / 3 O 3 Precursor sol spin coating in step (2) Pt / Ti / SiO 2 / Si substrate, the coating procedure was set to low speed 600r / min, time 10s, high speed 4000r / min, spin coating time 30s, and BiFe 1 / 3 Sc 1 / 3 (Ni 0.5 Ti 0.5 ) 1 / 3 O 3 Precursor sol-gel film.
[0049] (4) BiFe 1 / 3 Sc 1 / 3 (Ni 0.5 Ti 0.5 ) 1 / 3 O 3 The precursor sol film was placed in a rapid annealing furnace for heat treatment: heating rate 17.5°C / s, drying at 200°C for 2 minutes, pyrolysis at 400°C for 5 minutes, and annealing at 550°C for 5 minutes.
[0050] (5) Repeat steps (3) and (4) 15 times to obtain a BiFe 1 / 3 Sc 1 / 3 (Ni 0.5 Ti 0.5 ) 1 / 3 O 3 film.
[0051] Example 5
[0052] BiFe2O3 was prepared by solid solution of Fe, Sc, Ga and Al in equal proportions at the B site. 1 / 4 Sc 1 / 4 Ga 1 / 4 Al 1 / 4 O 3 A method for producing a ferroelectric thin film, comprising the steps of:
[0053] (1)BiFe 1 / 4 Sc 1 / 4 Ga 1 / 4 Al 1 / 4 O 3 Preparation of precursor sol: 1.0673 g bismuth nitrate (Bi(NO 3 ) 3 ·5H 2 O) was added to 6 ml of ethylene glycol methyl ether (C 3 H 8 O 2 , 2moe) in beaker A, stir at 500r / min at room temperature (25°C), and after it is completely dissolved, add 0.2020g of ferric nitrate (Fe(NO 3 ) 3 9H 2 O), 0.1245 g scandium nitrate (Sc(NO 3 ) 3 ·xH 2 O) and 0.1876 g aluminum nitrate (Al(NO 3 ) 3 9H 2 O), and continue stirring until completely dissolved. In addition, 0.1835 g of gallium acetylacetonate (C 15 H 21 O 6Ga) was added to beaker B containing 4 ml of ethylene glycol methyl ether, and the heating temperature was set at 45-70 ° C and stirred for 10 min until it was completely dissolved. After the beakers A and B were completely dissolved and stirred for 30 min each, the two were mixed and 0.4025 ml of acetylacetone was added. After stirring for 4 h at room temperature, the solution was filtered and sealed in a reagent bottle and aged at room temperature for 48 hours to obtain a uniform and stable BiFe 1 / 4 Sc 1 / 4 Ga 1 / 4 Al 1 / 4 O 3 The precursor sol has a sol concentration of 0.2M and an excess of 10% of Bi.
[0054] (2) Substrate thermal activation treatment: First, Pt / Ti / SiO 2 After the Si substrate is cleaned and dried, it is placed in a rapid annealing furnace for annealing: the heating rate is 37.5°C / s, annealing at 400°C for 1 minute, and then cooled to room temperature in the furnace.
[0055] (3) BiFe obtained in step (1) 1 / 4 Sc 1 / 4 Ga 1 / 4 Al 1 / 4 O 3 Precursor sol spin coating in step (2) Pt / Ti / SiO 2 / Si substrate, the coating procedure was set to low speed 600r / min, time 10s, high speed 4000r / min, spin coating time 30s, and BiFe 1 / 4 Sc 1 / 4 Ga 1 / 4 Al 1 / 4 O 3 Precursor sol-gel film.
[0056] (4) BiFe 1 / 4 Sc 1 / 4 Ga 1 / 4 Al 1 / 4 O 3 The precursor sol film was placed in a rapid annealing furnace for heat treatment: heating rate 17.5°C / s, drying at 200°C for 2 minutes, pyrolysis at 400°C for 5 minutes, and annealing at 550°C for 5 minutes.
[0057] (5) Repeat steps (3) and (4) 15 times to obtain a BiFe 1 / 4 Sc 1 / 4 Ga 1 / 4 Al 1 / 4 O 3 film.
[0058] Example 6
[0059] BiFe2O3 was prepared by solid solution of Fe, Ga, Ni and Ti in the B site. 1 / 3 Ga 1 / 3 Ni 1 / 6 Ti 1 / 6 O 3 A method for producing a ferroelectric thin film, comprising the steps of:
[0060] (1)BiFe 1 / 3 Ga 1 / 3 (Ni 0.5 Ti 0.5 ) 1 / 3 O 3 Preparation of precursor sol: 1.0673 g bismuth nitrate (Bi(NO 3 ) 3 ·5H 2 O) was added to 6 ml of ethylene glycol methyl ether (C 3 H 8 O 2 , 2moe) in beaker A, stir at 500r / min at room temperature (25°C), and after it is completely dissolved, add 0.2694g of ferric nitrate (Fe(NO 3 ) 3 9H 2 O) and 0.0989 g nickel nitrate (Ni(NO 3 ) 2 6H 2 O), and continue stirring until completely dissolved. In addition, 0.2447 g of gallium acetylacetonate (C 15 H 21 O 6 Ga) was added to beaker B containing 4 ml of ethylene glycol methyl ether, the heating temperature was set at 45-70 ° C and stirred for 10 min until it was completely dissolved, and then 0.1 ml of titanium isopropoxide (Ti[OCH(CH 3 ) 2 ] 4 After the contents in beakers A and B are completely dissolved and stirred for 30 min each, the two are mixed and 0.4025 ml of acetylacetone is added. After stirring for 4 h at room temperature, the solution is filtered and sealed in a reagent bottle. After aging at room temperature for 48 h, a uniform and stable BiFe 1 / 3 Ga 1 / 3 Ni 1 / 6 Ti 1 / 6 O 3 Precursor sol.
[0061] (2) Substrate thermal activation treatment: First, Pt / Ti / SiO 2After the Si substrate is cleaned and dried, it is placed in a rapid annealing furnace for annealing: the heating rate is 37.5°C / s, annealing at 400°C for 1 minute, and then cooled to room temperature in the furnace.
[0062] (3) Using a sizing machine, the BiFe 1 / 3 Ga 1 / 3 (Ni 0.5 Ti 0.5 ) 1 / 3 O 3 Precursor sol spin coating in step (2) Pt / Ti / SiO 2 / Si substrate, the coating procedure was set to low speed 600r / min, time 10s, high speed 4000r / min, spin coating time 30s, and BiFe 1 / 3 Ga 1 / 3 (Ni 0.5 Ti 0.5 ) 1 / 3 O 3 Precursor sol-gel film.
[0063] (4) BiFe 1 / 3 Ga 1 / 3 (Ni 0.5 Ti 0.5 ) 1 / 3 O 3 The precursor sol film was placed in a rapid annealing furnace for heat treatment: heating rate 17.5°C / s, drying at 200°C for 2 minutes, pyrolysis at 400°C for 5 minutes, and annealing at 550°C for 5 minutes.
[0064] (5) Repeat steps (3) and (4) 15 times to obtain a BiFe 1 / 3 Ga 1 / 3 (Ni 0.5 Ti 0.5 ) 1 / 3 O 3 film.
[0065] Comparative Example 1
[0066] Preparation of pure phase BiFeO without self-polarization by using Fe as the B-site 3 The method of producing a polycrystalline piezoelectric film comprises the following steps:
[0067] (1)BiFeO 3 Preparation of precursor solution: 1.0673 g bismuth nitrate (Bi(NO 3 ) 3 ·5H 2 O) was added to 10 ml of ethylene glycol methyl ether (C 3 H 8 O 2, 2moe) in a beaker, stir at 500r / min at room temperature (25°C), and add 0.8081g of ferric nitrate (Fe(NO 3 ) 3 9H 2 O), continue stirring until completely dissolved. Add 0.8406g of citric acid, continue stirring at room temperature for 4h, filter the solution and seal it in a reagent bottle, and let it stand at room temperature for 48 hours to obtain a uniform and stable BiFeO 3 The precursor sol has a sol concentration of 0.2M and an excess of 10% of Bi.
[0068] (2) Substrate thermal activation treatment: First, Pt / Ti / SiO 2 After the Si substrate is cleaned and dried, it is placed in a rapid annealing furnace for annealing: the heating rate is 37.5°C / s, annealing at 400°C for 1 minute, and then cooled to room temperature in the furnace.
[0069] (3) BiFeO obtained in step (1) 3 Precursor sol spin coating in step (2) Pt / Ti / SiO 2 / Si substrate, the coating procedure was set to low speed 600r / min, time 10s, high speed 4000r / min, spin coating time 30s, and BiFeO 3 Precursor sol-gel film.
[0070] (4) The obtained BiFeO 3 The precursor sol film was placed in a rapid annealing furnace for heat treatment: heating rate 17.5°C / s, drying at 200°C for 2 minutes, pyrolysis at 400°C for 5 minutes, and annealing at 550°C for 5 minutes.
[0071] (5) Repeat step (4) 15 times to obtain a BiFeO layer with a thickness of about 250 nm. 3 film.
[0072] Comparative Example 2
[0073] Conventional doping modified bismuth ferrite-based BiFe2O3 without self-polarization properties was prepared by using Fe and Sc at the B site. 0.8 Sc 0.2 O 3 The method of producing a polycrystalline piezoelectric film comprises the following steps:
[0074] (1)BiFe 0.8 Sc 0.2 O 3 Preparation of precursor sol: 1.0673 g bismuth nitrate (Bi(NO 3 ) 3 ·5H 2O) was added to 10 ml of ethylene glycol methyl ether (C 3 H 8 O 2 , 2moe) in a beaker, stir at 500r / min at room temperature (25°C), and after it is completely dissolved, add 0.6465g of ferric nitrate (Fe(NO 3 ) 3 9H 2 O) and 0.0997 g scandium nitrate (Sc(NO 3 ) 3 ·xH 2 O), and continue stirring until completely dissolved. Then add 0.8826g of citric acid, continue stirring at room temperature for 4h, filter the solution and seal it in a reagent bottle, and let it stand at room temperature for 48 hours to obtain a uniform and stable BiFe 0.8 Sc 0.2 O 3 The precursor sol has a sol concentration of 0.2M and an excess of 10% of Bi.
[0075] (2) Substrate thermal activation treatment: First, Pt / Ti / SiO 2 After the Si substrate is cleaned and dried, it is placed in a rapid annealing furnace for annealing: the heating rate is 37.5°C / s, annealing at 400°C for 1 minute, and then cooled to room temperature in the furnace.
[0076] (3) BiFe obtained in step (1) 0.8 Sc 0.2 O 3 Precursor sol spin coating in step (2) Pt / Ti / SiO 2 / Si substrate, the coating procedure was set to low speed 600r / min, time 10s, high speed 4000r / min, spin coating time 30s, and BiFe 0.8 Sc 0.2 O 3 Precursor sol-gel film.
[0077] (4) The obtained BiFe 0.8 Sc 0.2 O 3 The precursor sol film was placed in a rapid annealing furnace for annealing treatment: heating rate 17.5°C / s, drying at 200°C for 2 minutes, pyrolysis at 400°C for 5 minutes, and annealing at 550°C for 5 minutes.
[0078] (5) Repeat step (4) 15 times to obtain a BiFe 0.8 Sc 0.2 O 3 film.
[0079] Test Case
[0080] (1) Multi-element equiproportional solid solution BiFeO 3 Phase structure and morphology characterization of polycrystalline thin films based on
[0081] The multi-element isotropic solid solution BiFeO prepared in Examples 1 to 6 3 The crystal structure and cross-sectional morphology of the BiFeO thin films were characterized using X-ray diffraction. 3 The base film was subjected to X-ray diffraction analysis, and the results were as follows Figure 3 As shown in a, the labels in the figure represent the chemical formulas of the various components, corresponding to Examples 1-6. Figure 3 a It can be seen that BiFeO 3 The crystallization and phase information of the polycrystalline thin film. The XRD scanning results show that all samples are mainly perovskite structures. In the perovskite phase, 100, 110 and 200 diffraction peaks exist. At the same time, pure phase BiFeO 3 The single 200 diffraction peak of the film is theoretically split into multiple peaks, which indicates the coexistence of local multiphases. This experimental design method is also a good way to optimize piezoelectric performance. In addition, XRD shows that these films have an obvious Arrhenius phase diffraction peak, as well as a small amount of Si peaks and a strong (111) oriented Pt peak.
[0082] The Bi(Fe 1 / 3 Sc 1 / 3 Ga 1 / 3 ) 0.99 Mn 0.01 O 3 The cross-sectional analysis of ferroelectric thin films is carried out by using a focused narrow high-energy electron beam to scan the sample, and through the interaction between the beam and the material, various physical information is stimulated, and this information is collected, amplified, and re-imaged to achieve the purpose of characterizing the microscopic morphology, atomic arrangement, etc. of the material. Figure 3 b shows the atomic image of a certain area and the superimposed stress distribution. It can be seen from the figure that the grown polycrystalline film has multi-element equiproportional solid solution BiFeO 3 There are a large number of dislocation prestress concentration areas in the base film. These dislocations and stresses have a pinning effect on the electric dipoles, which is the reason why these films have self-polarization characteristics. These dislocations correspond to the Arrhenius phase diffraction peaks shown in the above XRD.
[0083] In addition, the Bi(Fe 1 / 3 Sc 1 / 3 Ga 1 / 3 ) 0.99 Mn 0.01 O3 The cross-sectional analysis of the ferroelectric film shows that the grains of the grown polycrystalline film are granular, and the thickness of the 15-layer multi-element equiproportional solid solution BFO-based film is about 250nm. Figure 4 shown.
[0084] (2) Multi-element equiproportional solid solution BiFeO 3 Self-Polarized Piezoelectric Properties of Polycrystalline Thin Films Based on MgO
[0085] Use d 33 The tester measures the self-polarization piezoelectric coefficient of the film prepared in Examples 1-6. The specific method is to place the sample to be tested on the test platform to ensure stability. The test metal column is continuously in contact with the sample with a linear constant force (20g, 40g, 60g...). The mechanical stress on the sample film will cause the piezoelectric effect and cause the distribution of the surface charge of the piezoelectric material to change. By recording the charge change detected on the surface, a charge change curve can be generated to fit the piezoelectric coefficient d 33 The results are as follows Figure 5 As shown, it can be seen that the films prepared in Examples 1-6 exhibit similar characteristics and have good self-polarization properties. The amplitude of the film corresponding to Example 3 is the largest, which also shows that this component Bi(Fe 1 / 3 Sc 1 / 3 Ga 1 / 3 ) 0.99 Mn 0.01 O 3 The film has the best piezoelectric performance, up to 236pC / N. Figure 5 It can be seen that compared with commercial ScAlN (about 30pC / N), the piezoelectric coefficients of the films prepared in Examples 1-6 are improved to varying degrees, ensuring their good performance in using piezoelectricity as sensors for both transmission and reception, allowing MEMS to utilize this excellent self-polarization piezoelectric property for actuation or sensing functions.
[0086] (3) Pure phase and conventional doping regulation of BiFeO 3 Characterization of Phase and Self-Polarized Piezoelectric Properties of Polycrystalline Thin Films
[0087] Compared with Examples 1 to 6, Comparative Examples 1 and 2 prepared pure phase BiFeO 3 Polycrystalline thin film and ordinary Sc doped (non-multi-element isotropic solid solution) BiFeO 3 The ferroelectric thin film was prepared and its crystal structure and self-polarized piezoelectric properties were characterized. Figure 6-7 As shown, from Figure 6 It can be seen from a and 7a that both comparison samples are mainly perovskite structures. In the perovskite phase, 100, 110 and 200 diffraction peaks all exist. At the same time, with the multi-element equiproportional solid solution BiFeO 3Different from the base ferroelectric film, the 200 diffraction peak is a theoretical R phase single peak, which does not have the characteristics of phase coexistence. At the same time, due to the absence of Arrhenius phase dislocation, this type of film does not have self-polarization characteristics, d 33 The test has no valid signal.
[0088] The above is only a preferred embodiment of the present invention, and the present invention is not limited to the above embodiments. It is understood that other improvements and changes directly derived or associated by those skilled in the art without departing from the spirit and concept of the present invention should be considered to be included in the protection scope of the present invention.
Claims
1. A method for preparing a bismuth ferrite-based film with high self-polarization piezoelectric performance by multi-element isotropic solid solution, characterized in that: The following steps are involved: (1) Preparation of sol: dissolving the raw materials in an organic solvent according to the stoichiometric ratio of multi-element equipotent solid solution BiFeO3, then adding a chemical chelating stabilizer, stirring until the mixture is uniform, filtering, sealing, and standing at room temperature for aging to obtain a clear, transparent, uniform and stable multi-element equipotent solid solution BiFeO3 precursor sol, wherein the multi-element equipotent solid solution BiFeO3 is a BiFeO3-based compound in which the B position is replaced by three or more cations, and the replacement method is that all the replacement cations are replaced in equal proportion or according to the weighted stoichiometric ratio, and the replacement cations are selected from Fe 3+ Sc 3+ , Ga 3+ 、Al 3+ , Mn 3+ 、Ni 2+ and Ti 4+ More than three of the following; (2) Spin coating: a multi-element equipotent BiFeO3 precursor sol is spin-coated on a substrate to form a film, and then the substrate coated with the multi-element equipotent BiFeO3 precursor sol is initially cured at 150±5°C to obtain a multi-element equipotent BiFeO3 precursor sol film; (3) Heat treatment: The substrate coated with the multi-element isomeric solid solution BiFeO3 precursor sol film in step (3) is heat treated by first drying at 120°C to 300°C for 30s to 2min, then pyrolyzing at 200°C to 500°C for 1 to 5min, and finally annealing at 500°C to 900°C for 1 to 15min. After cooling, a multi-element isomeric solid solution BiFeO3-based piezoelectric film is obtained.
2. The method according to claim 1, characterized in that In step (1), the organic solvent is selected from one or a combination of ethylene glycol methyl ether, acetic acid and ethylene glycol, the chemical chelating stabilizer is one or a combination of acetylacetone and citric acid, and the molar ratio of the chemical chelating stabilizer to the cations in the multi-element equal-ratio solid solution BiFeO3 is 1:
1.
3. The method according to claim 1, characterized in that In step (1), the stirring temperature is 25-80° C., the stirring time is 0.5-1 h, and the concentration of the multi-element equipotential solid solution BiFeO3 precursor sol is 0.01-0.5 mol / L.
4. The method according to claim 1, characterized in that In step (1), the multi-element equiproportional solid solution BiFeO3 is BiFe 1 / 3 Sc 1 / 3 Ga 1 / 3 O3、Bi(Fe 1 / 3 Sc 1 / 3 Ga 1 / 3 ) 0.99 Al 0.01 O3、Bi(Fe 1 / 3 Sc 1 / 3 Ga 1 / 3 ) 0.99 Mn 0.01 O3、BiFe 1 / 3Sc 1 / 3 (Ni 0.5 Ti 0.5 ) 1 / 3 O3、BiFe 1 / 4 Sc 1 / 4 Ga 1 / 4 Al 1 / 4 O3 or BiFe 1 / 3 Ga 1 / 3 (Ni 0.5 Ti 0.5 ) 1 / 3 O3.
5. The method according to claim 1, characterized in that In step (1), the raw materials are bismuth nitrate and a combination of three or more of ferric nitrate, scandium nitrate, gallium acetylacetonate, aluminum nitrate, manganese acetate, nickel nitrate and titanium isopropoxide.
6. The method according to claim 1, characterized in that In step (2), the spin coating method is to first spin coat at a low speed of 200-800 r / min for 5s-20s, and then spin coat at a high speed of 2000-8000 r / min for 20-40s.
7. The method according to claim 1, characterized in that In step (2), the initial curing time is 10s~2min.
8. The method according to claim 1, characterized in that In step (3), the heating rate is 10-150°C / s, the cooling rate is 0.5-3°C / s, and the heat treatment atmosphere is air, oxygen or nitrogen.
9. The method according to claim 1, characterized in that: The thickness of the multi-element equal-ratio solid solution BiFeO3-based piezoelectric film is regulated by controlling the number of repetitions of step (2) and step (3), and the number of repetitions is 2 to 50 times.
10. A bismuth ferrite-based thin film with high self-polarization piezoelectric properties obtained by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
GdSrMnCo codoped bismuth ferrite multiferroic film and making method thereof
CN107032631A
HoSrMnZn co-doped bismuth ferrite multiferroic film and preparation method thereof
CN107082579A
HoSrMnZncodopedbismuth ferrateferroelectric film with stable ferroelectricity in high electric field and preparation method thereof
CN107140971A
Manufacturing method of ceramic film, manufacturing method of piezoelectric element, manufacturing method of liquid injection head, and manufacturing method of liquid injection device
JP2012243837A
Method for producing functional device and apparatus for producing functional device
WO2013069686A1
